3х-у=3, 2. 2х-3у=1, 3. 2х+у=1, 4. х+у=6,
3х-2у=0. 3х+у=7. 5х+2у=0. 5х-2у=9.
5. х+5у=7, 6. х+у=7, 7. 4х-3у=-1, 8. х+2у=-2,
3х+2у=-5. 5х-7у=11. х-5у =4. 3х-у=8.
9. 2х-5у=-7, 10. х-у=3, 11. 3х-5у=16, 12. 2х+3у=-7,
х-3у=-5. 3х+4у=2. 2х+у=2. х-у=4.
13. 2х+5у=-7, 14. х-3у=8, 15. 2х-3у=5, 16. х-4у=-1,
3х-у=15. 2х-у=6. х-6у=-2. 3х-у=8.
17. 5х-4у=12, 18. 6х+у=5, 19. 2х-3у=11, 20. х-6у=-2,
х-5у=-6. 2х-3у=-5. 5х+у=2. 2х+3у=11.
21. 3х-2у=16, 22. 2х+3у=3, 23. 4х-2у=-6, 24. 3х+2у=8,
4х+у=3. 5х+6у=9. 6х+у==11. 2х+6у=10.
25. 5х+у==14, 26. 3х-2у=5, 27. х+4у=7, 28. 2х-3у=5,
3х-2у=-2. 2х+5у=16. х-2у=-5. 3х+2у=14.
29. х-2у=7, 30. 4х-6у=26, 31. х+3у=7, 32. 8х+3у=-21,
х+2у=-1. 5х+3у=1. х+2у=5. 4х+5у=-7.
33. х-2у=8, 34. 8х+2у=11, 35. 2х-у=13, 36. 7х+3у=1,
х-3у=6. 6х-4у=11. 2х+3у=9. 2х-6у=-10.
37. 2х+3у=10, 38. 3х-2у=5, 39. 2х+у=-5, 40. 2х+3у=1,
х-2у=-9. 5х+4у=1. х-3у=-6. 6х-2у=14.
1) Log3 4 - log3 16 + log3 4/9= Log3 4/ 16 + log3 4/9=Log3 ((4/16)*( 4/9))= Log3 1/9=
Log3 (3)^-2= -2
2) 2 log7 27 – log7 81-2 log7 21=log7 27^2 / 81-2 log7 21= log7 729/ 81- log7 21 ^2= log7 9- log7 21 ^2 = log7 (9/ 441)= log7 (1/ 49) = log7 (7^-2)=-2
3) 2 log2 8 +log2 15/4 – log2 15=log2 (8^2*(15/4)) – log2 15= log2 ((64*15)/4) – log2 15 =
log2 (16*15) – log2 15 = log2 ((16*15)/15)= log2 (16)= log2 (2^4)=4
4) log3 7 * log4 81 * log7 2= log4 81 * log7 2*1/ log7 3= log4 3^4 *( log7 2/ log7 3 )=
4* log4 3 * log3 2=4* log3 2*(1/ log3 4) = 4* log3 2*(1/ log3 2^2) = 4* log3 2*(1/ 2 log3 2)= (4* log3 2)/ (2 log3 2) =4/2=2
5) Lg3(log3 25+log3 2-log3 5) = Lg3(log3 (25* 2)-log3 5)= Lg3(log3 50/ 5) = Lg3*log3 10 = log10 3* log3 10= log10 3/ log10 3=1